A polyester matt film master batch slice, a preparation method and application thereof

CN121108694BActive Publication Date: 2026-10-09JIANGSU YIERMAN NEW MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511318789.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-09-16
Publication Date
2026-10-09
Estimated Expiration
2045-09-16

AI Technical Summary

Technical Problem

这些聚集体在薄膜拉伸过程中易脱离基体,造成膜面出现“白点”(聚集体暴露)或“针孔”(聚集体脱落留下的空隙),高端标签领域对膜面瑕疵率要求≤0.1个/m2,传统方案难以满足

Benefits of technology

本发明通过双改性SiO2的优异相容性与EMA-GMA的熔体调节作用,在消光剂添加量10-20wt%的高比例下,仍能保持熔体粘度增幅≤30%,滤网压差升高速率≤0.5bar・h-1,可满足24小时连续稳定生产,相较于传统方案,生产效率大幅度提升,换网成本降低。利用本发明母粒制得的BOPET亚光膜,关键性能指标远超现有技术,同时低成本、易产业化,设备适配性强。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application discloses a kind of polyester matt film master batch slice and its preparation method and application, belong to high polymer functional material field.The titanium-free bright PET is used as matrix, KH-570 is matched with PMMA-PBMA double-layer modified SiO2 extinction agent, EMA-GMA compatibility agent etc., and the master batch is prepared by side-feeding double-screw extrusion;The master batch is mixed with PET according to 10-20:80-90, and 12-50 μm BOPET matt film is prepared by three-layer co-extrusion, bidirectional stretching.The master batch can be continuously produced for 24 hours, the film 60 degree gloss is less than or equal to 15GU, tensile strength is greater than or equal to 210MPa, and it is environmentally friendly and compliant.The scheme solves the existing technology extinction-processing-mechanical balance problem, adapts to existing equipment, and has clear industrialization prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer materials technology, specifically proposing a masterbatch chip for polyester matte film, its preparation method, and its application. Background Technology

[0002] Biaxially oriented polyester (BOPET) matte film is increasingly in demand in high-end labels, photovoltaic backsheets, electronic packaging, and environmentally friendly packaging due to its low gloss, high haze appearance, and excellent mechanical properties. Functional masterbatch, as the core raw material for preparing BOPET matte film, directly determines the quality and production stability of the matte film. Therefore, the development of high-performance masterbatch for polyester matte film has become a key focus of the industry.

[0003] Current mainstream matting solutions in the industry mainly rely on "inorganic powder blending modification," which involves adding unmodified inorganic particles such as SiO2, BaSO4, or CaCO3 to the PET matrix, utilizing the micro-roughness structure formed by these particles on the film surface to achieve a matting effect. This solution has the following key problems: Poor interfacial compatibility and frequent film defects: Inorganic powders are rich in hydroxyl groups and are strongly hydrophilic, while PET is a hydrophobic polymer. The significant difference in interfacial tension between the two (PET surface tension is approximately 42 mN / m, while unmodified SiO2 surface tension is approximately 72 mN / m) causes the powder to easily agglomerate in the PET melt, forming aggregates with a diameter >5 μm. These aggregates easily detach from the substrate during film stretching, resulting in "white spots" (exposed aggregates) or "pinholes" (voids left by detached aggregates) on the film surface. High-end label applications require a film defect rate of ≤0.1 defects / m. 2 Traditional solutions are insufficient to meet these requirements.

[0004] Poor processing stability and low production efficiency: To achieve the ideal matte finish (60° gloss ≤ 25GU), the amount of inorganic powder added needs to reach 5-25wt%, but a high addition amount will cause the PET melt viscosity to increase sharply (when adding 15wt% unmodified SiO2, the melt viscosity can increase by more than 80%). The increase in viscosity directly leads to a rapid increase in the filter screen pressure difference during extrusion (the rate of increase is ≥ 1.5 bar·h). -1 Typically, continuous production for ≤8 hours requires a shutdown and screen replacement. This not only interrupts the production process but also causes film thickness deviations to exceed the standard (±5%) due to temperature fluctuations during the screen replacement process, further reducing the product qualification rate.

[0005] Subsequent processing performance deteriorates, and mechanical strength is insufficient: The aggregated inorganic particles have weak adhesion to the PET matrix, and particles are prone to detachment during subsequent aluminizing (an essential process for photovoltaic backsheets and electronic packaging films) or adhesive coating (an essential process for label films). This leads to a decrease in the adhesion of the aluminized layer (peel strength ≤3N / 15mm, industry requirement ≥5N / 15mm) or loss of gloss in the adhesive coating layer (gloss recovers to above 30GU). At the same time, the high content of inorganic particles will disrupt the continuity of the PET molecular chain, resulting in a significant decrease in the mechanical properties of the film—tensile strength is usually ≤190MPa and elongation at break ≤95%, which cannot meet the mechanical stability requirements for long-term outdoor use of photovoltaic backsheets (tensile strength ≥200MPa, elongation at break ≥100%).

[0006] To address the aforementioned issues, some studies have attempted to treat inorganic powders using "silane coupling agent monolayer modification" (e.g., using silane coupling agents such as KH-550 and KH-570), improving the compatibility of the powder with PET through the organic functional groups of the coupling agent. However, this improvement method still has insurmountable shortcomings: Poor coating stability and failure at high temperatures: The silane coupling agent and the hydroxyl groups on the SiO2 surface only form monodentate coordination bonds. Under the high temperature (240-260℃) and strong shear environment of twin-screw extrusion, the coordination bonds are prone to breakage, causing the coating layer to fall off and triggering agglomeration again. Moreover, the thickness of the single-layer organic coating is only 1-2nm, which cannot effectively buffer the interfacial stress between the particles and the PET matrix, and it is still difficult to avoid the decline in mechanical properties.

[0007] Limited matting effect and difficulty in balancing performance: Single-layer modification can only reduce the gloss of the film from 60° to 20-25 GU, which cannot meet the demand of high-end labels for "matte texture" (gloss ≤15 GU); if the amount of powder added is further increased (≥20wt%), it will again cause melt fracture (sharkskin-like defects on the surface of the melt during extrusion) and die accumulation (melt accumulates at the die lip, causing stripes on the film surface), making it impossible to achieve stable production.

[0008] Environmental and cost issues: Some improvement solutions require the use of organic solvents such as toluene and xylene as dispersion media to enhance the coating effect. This not only raises VOC emissions (which do not meet EU CE certification requirements) but also increases solvent recovery costs. Furthermore, some imported silane coupling agents (such as KH-560) are expensive, leading to a 15-20% increase in masterbatch production costs, which is not conducive to industrialization.

[0009] In summary, existing technologies cannot simultaneously solve the synergistic problem of "high matte finish, excellent mechanical properties, stable processability and environmental compliance". There is an urgent need to develop a new masterbatch technology for polyester matte film to meet the usage needs and industrialization requirements of downstream high-end fields. Summary of the Invention

[0010] In view of this, the purpose of this invention is to overcome the defects of the prior art and provide a masterbatch chip for polyester matte film, its preparation method and application. Through the synergistic technical solution of "dual modified matte agent design - compatibilizer system optimization - preparation process innovation", a comprehensive breakthrough is achieved in masterbatch processing stability, film performance and environmental protection.

[0011] The technical solution of this invention is implemented as follows: This invention provides a masterbatch prepared using a "double-layer chemically bonded modified SiO2" as the matting core and a "ethylene-methyl acrylate-glycidyl methacrylate (EMA-GMA) terpolymer" as a compatibilizer, through a two-stage twin-screw extrusion process of "side feeding and vacuum devolatilization". This masterbatch, after being blended with glossy PET chips, can be biaxially stretched to obtain a low-gloss, high-mechanical-performance BOPET matte film. The entire solution requires no solvent, uses domestically produced raw materials, can be directly integrated into existing production lines, and has immediate industrialization capability.

[0012] The masterbatch chips of the present invention, by weight, comprise the following components: Glossy PET resin: intrinsic viscosity is 0.62 dL·g -1 The water bottle grade titanium-free glossy PET resin is used in quantities of 70-90 parts. This PET was chosen because its intrinsic viscosity falls within the balance range between processing flowability and mechanical properties—too low a viscosity (<0.55 dL·g) is undesirable. -1 This will cause a decrease in the tensile strength of the film; excessively high values ​​(>0.70 dL·g) will lead to a decrease in the tensile strength of the film. -1 Adding titanium will increase the melt viscosity, which is not conducive to the dispersion of the matting agent. The "titanium-free" design can avoid the interference of TiO2 (a component in conventional light-shielding PET) on the matting effect (TiO2 will reflect light, causing the gloss to rise). At the same time, the water bottle grade PET is made from recycled materials and meets environmental protection requirements.

[0013] Double-modified SiO2 matting agent: Used in amounts of 5-20 parts, it is the core component for achieving low gloss and high dispersibility. It has a double-layer chemically bonded structure of "silane coupling agent coating layer + acrylate copolymer coating layer," with the following specific characteristics: The substrate is precipitated SiO2 with D50 = 1.5 μm and BET = 180 μm. 2 / g, this particle size can form a uniform micro-rough structure on the film surface (roughness Ra=0.15-0.20μm), which meets the extinction requirements; the high specific surface area provides sufficient reaction sites for double-layer coating.

[0014] The inner layer is a 3-methacryloyloxypropyltrimethoxysilane (KH-570) coating layer: the alkoxy group of the silane coupling agent undergoes a condensation reaction with the hydroxyl group on the surface of SiO2 to form a stable Si-O-Si covalent bond. At the same time, the carbon-carbon double bond of the coupling agent can undergo a polymerization reaction with the outer polymer to achieve "inner layer chemical bonding".

[0015] The outer layer is a copolymer of methyl methacrylate (MMA) and butyl methacrylate (BMA) (PMMA-PBMA) coating layer: the high hardness of MMA can improve the interfacial bonding force between the matting agent and PET, and the flexibility of BMA can buffer the interfacial stress during the stretching process. The two work together to improve both dispersibility and mechanical properties.

[0016] EMA-GMA terpolymer: Used in amounts of 2-5 parts as a compatibilizer and melt flow modifier. Its key characteristics are: GMA content 6wt%, melt flow rate (MI) = 8g / 10min. The epoxy groups in GMA can undergo a chain-opening reaction with the terminal carboxyl groups of PET to form a long-chain branched structure called "PET-g-EMA". This structure can significantly reduce the melt viscosity (the melt viscosity increases by ≤30% when 3 parts are added), while strengthening the interfacial bonding between PET and the double-modified SiO2.

[0017] A suitable MI value (8g / 10min) can ensure that it matches the flowability of the PET melt. If the MI is too high (>12g / 10min), the compatibilizer will migrate to the film surface, affecting the subsequent metallization performance; if it is too low (<5g / 10min), it will increase the melt viscosity, which is not conducive to processing.

[0018] Antioxidant: A 1:1 mixture of antioxidant 1010 and antioxidant 168, used in amounts of 0.2-0.5 parts. Antioxidant 1010 is a hindered phenolic primary antioxidant that can capture free radicals; antioxidant 168 is a phosphite secondary antioxidant that can decompose hydroperoxides. The combination of the two forms a synergistic antioxidant effect, preventing thermo-oxidative aging (intrinsic viscosity decrease ≤0.02 dL·g) of PET during high-temperature extrusion (240-260℃). -1 ).

[0019] Lubricant: Ethylene bis-stearamide (EBS), dosage: 0.1-0.3 parts. Its function is to reduce the coefficient of friction between the melt and the screw and die, and reduce material accumulation at the die; at the same time, it can improve the pelletizing effect of the masterbatch and avoid particle adhesion (the particle packing density is stable when the moisture content is ≤50ppm).

[0020] In a second aspect, the present invention also provides a method for preparing the above-mentioned masterbatch chips for polyester matte film, which employs a two-step method of "dual-modified SiO2 preparation - two-stage twin-screw extrusion", the specific steps of which are as follows: Preparation of dual-modified SiO2 matting agent: Step ①: Dispersion pretreatment. Add 100 parts of precipitated SiO2 to a mixed solvent of 500 parts deionized water and 500 parts ethanol, and disperse ultrasonically for 30 minutes. Ethanol can reduce the surface tension of the solvent, and ultrasound (power 300W) can break the initial agglomeration of SiO2, ensuring uniform dispersion (particle size distribution Span≤1.2).

[0021] Step 2: Silane coupling agent coating (inner layer). Heat the dispersion to 60°C, add 5 parts of KH-570 dropwise, adjust the pH to 4.5 with acetic acid (this pH is the optimal condition for the hydrolysis and condensation of KH-570, which can improve the coating efficiency), and keep the reaction at this temperature for 2 hours to form the inner layer of silane coupling agent.

[0022] Step 3: Acrylic ester copolymer coating (outer layer). Add 0.5 parts ammonium persulfate (initiator) to the system, dropwise add a mixture of 3 parts MMA and 2 parts BMA monomers, purge with nitrogen gas for protection (to avoid monomer oxidation), and heat to 70°C for polymerization for 3 hours—the nitrogen atmosphere ensures uniform polymerization reaction and avoids local overheating that could lead to polymer crosslinking.

[0023] Step 4: Post-processing. The reaction product was cooled to room temperature, filtered (filter membrane pore size 0.45 μm), and vacuum dried at 120℃ for 4 hours (vacuum degree ≤ -0.09 MPa, to remove residual solvent) to obtain the double-modified SiO2 matting agent. The contact angle of this matting agent can reach 132° (unmodified SiO2 is only 28°), and the thermal weight loss at 800℃ is 12.3% (single-layer KH-570 modification is only 4.1%), proving that the coating layer is stable.

[0024] Extrusion preparation of masterbatch chips: Step ①: Raw material pretreatment. Dry the PET resin at 160℃ for 4 hours (moisture content ≤50ppm to avoid generating bubbles during extrusion); dry the double-modified SiO2 at 120℃ for 2 hours (to remove adsorbed water and avoid affecting melt flowability).

[0025] Step 2: Two-stage twin-screw extrusion. PET resin, antioxidant, and lubricant are added to the twin-screw extruder through the main feed port and melted in zones 1-4 (temperature 180-220℃). Low-temperature melting reduces PET thermal degradation. In zone 5 (side feed port, located after the melting section), double-modified SiO2 and EMA-GMA are added and mixed in zones 6-10 (temperature 240-260℃). Side feeding shortens the residence time of the matting agent in the high-temperature zone (≤3 minutes), avoiding thermal decomposition of the coating layer. At the same time, vacuum devolatilization (vacuum degree ≤ -0.08MPa) is activated to remove small molecules generated during the melting process (such as acetaldehyde generated by PET degradation).

[0026] Step 3: Pelletizing and Drying. After the melt is extruded through a die (2.5mm aperture), it is stretched underwater (water temperature 25℃, cooling rate 50℃ / s to ensure uniform particle crystallization), pelletized (3mm in length), and finally crystallized and dried at 120℃ for 4 hours to obtain masterbatch chips. The intrinsic viscosity drop of this masterbatch is ≤0.02dL・g. -1 This meets the requirements for subsequent stretching.

[0027] This invention also provides a masterbatch for the preparation of matte polyester film. The masterbatch chips of this invention are mixed with glossy PET chips at a weight ratio of 15:85, and a matte film is prepared using a three-layer co-extrusion biaxial stretching process. The specific steps are as follows: Melt co-extrusion: The mixed raw materials are melted at 250℃ (temperature gradient 230-250℃ to avoid local overheating) and extruded through a three-layer co-extrusion die (layers A / C are a masterbatch / PET mixture, layer B is pure PET, thickness ratio A:B:C=1:3:1) - the three-layer structure can reduce the amount of masterbatch used while ensuring the matting effect (the surface layer A / C contains matting agent) (cost optimization).

[0028] Casting: The melt is cast on a cooling drum at 25°C (cooling rate 100°C / s, forming an amorphous PET casting for easy subsequent stretching), with a casting thickness of 120-250μm (adjusted according to the final film thickness).

[0029] Biaxial stretching: longitudinal stretching is performed at 85°C (near the glass transition temperature of PET, where the stretching effect is optimal) and stretches the film 4.0 times in the machine direction; transverse stretching is performed at 110°C (higher than the longitudinal stretching temperature to avoid film shrinkage) and stretches the film 4.0 times in the transverse direction. Biaxial stretching can orient the PET molecular chains and improve the mechanical properties of the film.

[0030] Post-processing: The stretched film is heat-set at 230℃ for 5 seconds (to eliminate internal stress and improve dimensional stability), then corona-treated (surface tension ≥42dyn / cm, to meet the requirements of subsequent adhesive coating), and finally wound up (winding tension 50N to avoid wrinkling of the film) to obtain a 12-50μm BOPET matte film.

[0031] The present invention has the following advantages over the prior art: This invention, through the excellent compatibility of dual-modified SiO2 and the melt conditioning effect of EMA-GMA, maintains a melt viscosity increase of ≤30% and a filter screen pressure difference increase rate of ≤0.5 bar·h even at a high proportion of matting agent addition of 10-20 wt%. -1 This technology enables continuous and stable production for 24 hours, significantly improving production efficiency and reducing screen replacement costs compared to traditional methods. The BOPET matte film produced using the masterbatch of this invention exhibits key performance indicators far exceeding existing technologies, while also being low-cost, easily industrialized, and highly adaptable to various equipment. Detailed Implementation

[0032] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0033] Example 1 Masterbatch preparation Step 1: Preparation of the dual-modified SiO2 matting agent. 100 parts by weight of precipitated SiO2 (D50=1.5μm, BET=180m² / g) were added to a mixed solvent consisting of 500 parts by weight of deionized water and 500 parts by weight of ethanol. The mixture was ultrasonically dispersed for 30 minutes using a 300W ultrasonic device to obtain a uniform dispersion. The dispersion was transferred to a reaction vessel, heated to 60℃, and 5 parts by weight of 3-methacryloyloxypropyltrimethoxysilane (KH-570) were slowly added dropwise. The pH was adjusted to [value missing] with acetic acid. 4.5, keep the reaction at a constant temperature for 2 hours; add 0.5 parts by weight of ammonium persulfate to the reactor, and dropwise add a mixture of 3 parts by weight of methyl methacrylate (MMA) and 2 parts by weight of butyl methacrylate (BMA) monomers. Purge with nitrogen for protection, heat to 70℃ and keep the temperature for polymerization for 3 hours; stop heating and cool to room temperature, filter with a 0.45μm filter membrane, and dry the filter cake in a vacuum drying oven at 120℃ and a vacuum degree ≤-0.09MPa for 4 hours to obtain the double-modified SiO2 matting agent.

[0034] Step 2: Raw material pretreatment. 85 parts by weight of titanium-free glossy PET resin (intrinsic viscosity 0.62 dL·g) -1 Dry at 160℃ for 4 hours (moisture content ≤50ppm); dry 10 parts by weight of the double-modified SiO2 matting agent obtained in step 1 at 120℃ for 2 hours; prepare 3 parts by weight of EMA-GMA (GMA content 6wt%, MI=8g / 10min), 0.3 parts by weight of antioxidant 1010 / 168 (1:1 compound), and 0.2 parts by weight of EBS lubricant.

[0035] Step 3: Two-stage twin-screw extrusion. PET resin, antioxidant, and EBS are added to the twin-screw extruder through the main feed port and melted in zones 1-4 (temperature 180-220℃). Pre-dried double-modified SiO2 and EMA-GMA are added to the side feed port in zone 5 and mixed in zones 6-10 (temperature 240-260℃) while vacuum devolatilization (vacuum degree -0.08MPa). The melt is extruded through a die with a 2.5mm diameter, drawn into strands underwater at 25℃ (cooling rate 50℃ / s), cut into 3mm long particles, and finally crystallized and dried at 120℃ for 4 hours to obtain masterbatch chips.

[0036] Thin film preparation Step 1: Raw material mixing. The masterbatch chips obtained in Example 1 are mixed with glossy PET chips at a weight ratio of 15:85 until homogeneous.

[0037] Step 2: Melt co-extrusion. The mixed raw materials are melted at 250℃ (temperature gradient 230-250℃) and extruded through a three-layer co-extrusion die (layers A / C are a mixed system, layer B is pure PET, and the thickness ratio A:B:C=1:3:1).

[0038] Step 3: Casting and Stretching. The melt is cast into sheets on a cooling drum at 25°C (cooling rate 100°C / s, sheet thickness 180μm); it is then stretched 4.0 times longitudinally at 85°C and 4.0 times transversely at 110°C.

[0039] Step 4: Post-processing. The stretched film is heat-set at 230℃ for 5 seconds, then corona treated (surface tension ≥ 42 dyn / cm) and wound up (winding tension 50 N) to obtain a 25 μm thick matte BOPET film.

[0040] Example 2 Masterbatch preparation Step 1: The preparation of the double-modified SiO2 matting agent is the same as in Example 1.

[0041] Step 2: Raw material pretreatment. Prepare 80 parts by weight of titanium-free glossy PET resin (intrinsic viscosity 0.62 dL·g). -1 ), 15 parts by weight of double-modified SiO2, 4 parts by weight of EMA-GMA, 0.4 parts by weight of antioxidant 1010 / 168, and 0.2 parts by weight of EBS, with pretreatment conditions the same as in Example 1.

[0042] Step 3: Two-stage twin-screw extrusion. Process parameters are the same as in Example 1, with continuous production for 36 hours, during which the melt state and filter pressure changes are monitored in real time.

[0043] Thin film preparation Except for “cast thickness 220μm, final film thickness 30μm”, the other steps are the same as in Example 1.

[0044] Example 3 Masterbatch preparation Step 1: The preparation of the double-modified SiO2 matting agent is the same as in Example 1.

[0045] Step 2: Raw material pretreatment. Prepare 75 parts by weight of titanium-free glossy PET resin (intrinsic viscosity 0.62 dL·g). -1 ), 20 parts by weight of double-modified SiO2, 5 parts by weight of EMA-GMA, 0.5 parts by weight of antioxidant 1010 / 168, and 0.3 parts by weight of EBS, with pretreatment conditions the same as in Example 1.

[0046] Step 3: Two-stage twin-screw extrusion is the same as in Example 1.

[0047] Thin film preparation Except for “cast thickness 350μm, final film thickness 50μm”, the other steps are the same as in Example 1.

[0048] Example 4 Masterbatch preparation Step 1: The preparation of the double-modified SiO2 matting agent is the same as in Example 1.

[0049] Step 2: Raw material pretreatment. Prepare 90 parts by weight of titanium-free glossy PET resin (intrinsic viscosity 0.62 dL·g). -1 5 parts by weight of double-modified SiO2, 2 parts by weight of EMA-GMA, 0.2 parts by weight of antioxidant 1010 / 168, and 0.1 parts by weight of EBS, with pretreatment conditions the same as in Example 1.

[0050] Step 3: Two-stage twin-screw extrusion is the same as in Example 1.

[0051] Thin film preparation Except for the "cast thickness of 80μm and final film thickness of 12μm", the other steps are the same as in Example 1.

[0052] Example 5 Masterbatch preparation Step 1: The preparation of the double-modified SiO2 matting agent is the same as in Example 1.

[0053] Step 2: Raw material pretreatment. Prepare 82 parts by weight of titanium-free glossy PET resin (intrinsic viscosity 0.70 dL·g). -1 ), 12 parts by weight of double-modified SiO2, 3 parts by weight of EMA-GMA, 0.3 parts by weight of antioxidant 1010 / 168, and 0.2 parts by weight of EBS, with pretreatment conditions the same as in Example 1.

[0054] Step 3: Two-stage twin-screw extrusion is the same as in Example 1.

[0055] Thin film preparation Except for the "cast thickness of 140μm and final film thickness of 20μm", the other steps are the same as in Example 1.

[0056] Comparative Example 1 Masterbatch preparation Step 1: Raw material pretreatment. Prepare 85 parts by weight of titanium-free glossy PET resin (intrinsic viscosity 0.62 dL·g). -1 10 parts by weight of unmodified SiO2 (D50=1.5μm, dried at 120℃ for 2 hours), 0.3 parts by weight of antioxidant 1010 / 168, and 0.2 parts by weight of EBS (without EMA-GMA).

[0057] Step 2: Twin-screw extrusion. All raw materials are fed into the twin-screw extruder through the main feed port. The temperature range is 180-260℃, and the vacuum degree is -0.08MPa. The remaining processes are the same as in Example 1.

[0058] Thin film preparation Same as Example 1 Comparative Example 2 Masterbatch preparation Step 1: Preparation of monolayer modified SiO2. 100 parts by weight of precipitated SiO2 were dispersed in a water-ethanol mixed solvent (same as in Example 1), sonicated for 30 minutes, heated to 60°C, 5 parts by weight of KH-570 were added dropwise, the pH was adjusted to 4.5, the reaction was carried out for 2 hours, filtered and dried (same as in Example 1) to obtain monolayer modified SiO2 coated only with KH-570.

[0059] Step 2: Raw material pretreatment and extrusion. Prepare 85 parts by weight of PET resin, 10 parts by weight of single-layer modified SiO2, 0.3 parts by weight of antioxidant, and 0.2 parts by weight of EBS (EMA-GMA-free). The extrusion process is the same as in Comparative Example 1.

[0060] Thin film preparation Same as Example 1 Comparative Example 3 Masterbatch preparation Step 1: The preparation of double-modified SiO2 is the same as in Example 1.

[0061] Step 2: Raw material pretreatment and extrusion. Prepare 85 parts by weight of PET resin, 10 parts by weight of double-modified SiO2, 0.3 parts by weight of antioxidant, and 0.2 parts by weight of EBS (EMA-GMA-free). The extrusion process is the same as in Example 1.

[0062] Thin film preparation Same as Example 1 Comparative Example 4 Masterbatch preparation Step 1: The preparation of double-modified SiO2 is the same as in Example 1.

[0063] Step 2: Raw material pretreatment. Same as Example 1 (85 parts by weight of PET, 10 parts by weight of double-modified SiO2, 3 parts by weight of EMA-GMA, etc.).

[0064] Step 3: Main feed extrusion. PET resin, double-modified SiO2, EMA-GMA, antioxidant, and EBS are all fed into the twin-screw extruder through the main feed port. The temperature range is 180-260℃, and the vacuum degree is -0.08MPa. The remaining processes are the same as in Example 1.

[0065] Thin film preparation Same as Example 1 Comparative Example 5 Masterbatch preparation Step 1: Preparation of monolayer modified SiO2 as in Comparative Example 2.

[0066] Step 2: Raw material pretreatment and extrusion. Prepare 85 parts by weight of PET resin, 10 parts by weight of single-layer modified SiO2, 3 parts by weight of EMA-GMA, 0.3 parts by weight of antioxidant, and 0.2 parts by weight of EBS. The extrusion process is the same as in Example 1.

[0067] Thin film preparation Same as Example 1 Performance verification Performance verification of all embodiments and comparative examples was performed according to the following standardized procedures, and the testing standards conformed to industry norms: Masterbatch melt viscosity increase test: A Haake rheometer (model HAAKEPolylabOS) was used at 260℃ and a shear rate of 100s. -1 The masterbatch melt viscosity was measured under the same conditions; the increase was calculated based on the melt viscosity of pure PET resin of the same batch under the same conditions (increase = (masterbatch viscosity - pure PET viscosity) / pure PET viscosity × 100%).

[0068] Masterbatch filter pressure rise rate test: During twin-screw extrusion production, the pressure difference before and after the filter screen is recorded in real time by the extruder pressure sensor, and the pressure difference change per unit time is calculated (unit: bar·h). -1 ).

[0069] Masterbatch intrinsic viscosity drop test: The intrinsic viscosity of the masterbatch was measured at 25°C in a phenol-tetrachloroethane (1:1) solvent using an Ubbelohde viscometer; the viscosity drop was calculated by comparing it with the intrinsic viscosity of the raw material PET resin (viscosity drop = raw material PET viscosity - masterbatch viscosity).

[0070] 60° gloss test of thin film: According to GB / T8807-1988, use a BYK-Gardner micro-TRI-gloss gloss meter to randomly select 5 points on the surface of the thin film and take the average value (unit: GU).

[0071] Thin film haze test: According to GB / T2410-2008, use a WGT-S haze meter to randomly select 5 points on the thin film surface for testing, and take the average value (unit: %).

[0072] Film tensile strength and elongation at break test: Prepare dumbbell-shaped 1A specimens according to GB / T1040.3-2006, and test 5 times using an Instron 5969 universal testing machine (tensile speed 50 mm / min), and take the average value (strength unit: MPa, elongation unit: %).

[0073] SiO2 shedding rate test of thin film: The initial Si element content of the thin film was determined by Thermo Scientific K-Alpha X-ray photoelectron spectroscopy; after applying 5N pressure with 3M 610 tape and then quickly peeling it off, the process was repeated 10 times, and the Si content was measured again to calculate the shedding rate (shedding rate = (initial Si content - Si content after peeling) / initial Si content × 100%).

[0074] Tensile strength retention rate test after film aging: Place the film in a Q-SunXe-3-HSS xenon lamp aging chamber (85℃, 85%RH) for 1000 hours; test the tensile strength after aging according to step 6, and calculate the retention rate (retention rate = strength after aging / strength before aging × 100%).

[0075] Performance verification results Table 1 Performance verification results of the examples:

[0076] Table 2 Comparative Performance Verification Results

[0077] Examples 1-5 verify that the masterbatch of this invention, with double-layer modified SiO2 and EMA-GMA as its core, is prepared by a side-feed twin-screw process. With the addition of 3-25 parts by weight of double-modified SiO2, continuous production for 24 hours is possible, with a melt viscosity increase of ≤30%. The resulting 12-50μm BOPET matte film has a 60° gloss of ≤15GU and a tensile strength of ≥210MPa, meeting performance standards. In contrast, Comparative Examples 1-5 (unmodified / single-layer modified SiO2, no EMA-GMA, main feeder, etc.) show processing instability (e.g., continuous production ≤15h) and film performance degradation (e.g., tensile strength ≤200MPa) due to the absence of any key feature of this invention. This demonstrates that this solution is not a combination of existing technologies and effectively overcomes the balance problem of "matte finish-processing-mechanics".

[0078] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A masterbatch chip for polyester matte film, characterized in that, By weight, it includes the following components: The intrinsic viscosity is 0.55-0.70 dL. g -1 65-95 parts of titanium-free glossy PET resin; 3-25 parts of double-modified SiO2 matting agent; the double-modified SiO2 matting agent is a double-layer chemical bonded structure of silane coupling agent coating layer and acrylate copolymer coating layer, the silane coupling agent is a silane coupling agent containing carbon-carbon double bonds, and the acrylate copolymer is a copolymer of methacrylate monomers and butyl acrylate monomers. 1-6 parts of ethylene-acrylate-glycidyl methacrylate terpolymer; Antioxidant 0.1-0.8 parts; Lubricant 0.05-0.5 parts; The masterbatch slices are prepared by the following steps: S1. Preparation of double-modified SiO2 matting agent: Precipitated SiO2 is treated with silane coupling agent and then polymerized with acrylate monomers to form a double-layer coating structure. S2. A two-stage twin-screw extrusion process is adopted: the PET resin, antioxidant and lubricant are added to the main feed port and melted at 160-240℃; the pre-dried double-modified SiO2 matting agent and the terpolymer are added to the side feed port and mixed at 220-280℃. S3. Vacuum devolatilization is performed at a vacuum degree ≤ -0.06MPa; the masterbatch slices are obtained by underwater pelleting and crystallization drying.

2. The masterbatch slices as described in claim 1, characterized in that, The modified SiO2 matting agent has a particle size D50 of 1.0-2.0 μm and a specific surface area BET of 150-200 m². 2 g -1 .

3. The masterbatch slices as described in claim 1, characterized in that, The terpolymer is an ethylene-methyl acrylate-glycidyl methacrylate copolymer, wherein the mass content of glycidyl methacrylate is 4-8%, and the melt flow rate at 190℃ and 2.16kg is 5-12g / 10min.

4. A method for preparing masterbatch chips for polyester matte film as described in claim 1, characterized in that, Includes the following steps: S1. Preparation of double-modified SiO2 matting agent: Precipitated SiO2 is treated with silane coupling agent and then polymerized with acrylate monomers to form a double-layer coating structure. S2. A two-stage twin-screw extrusion process is adopted: PET resin, antioxidant, and lubricant are added to the main feed port and melted at 160-240℃; pre-dried double-modified SiO2 matting agent and terpolymer are added to the side feed port and mixed at 220-280℃. S3. Vacuum devolatilization is performed at a vacuum degree of ≤-0.06MPa; the masterbatch chips are obtained by underwater pelleting and crystallization drying.

5. The preparation method according to claim 4, characterized in that, The specific preparation process of the dual-modified SiO2 matting agent mentioned in step S1 is as follows: a. Disperse SiO2 in a water-alcohol mixed solvent and ultrasonically disperse for 10-60 min; b. Add a silane coupling agent containing carbon-carbon double bonds and react at 40-80℃ for 1-3 hours under pH 3.5-5.5 conditions; c. Add an initiator, then add a mixture of methacrylate and butyl acrylate dropwise, polymerize at 60-90℃ for 2-5 hours, and dry to obtain the final product.

6. The preparation method according to claim 5, characterized in that, The silane coupling agent mentioned in step b is 3-methacryloyloxypropyltrimethoxysilane, and the amount used is 3-8% of the weight of SiO2.

7. The preparation method according to claim 4, characterized in that, In step S2, the side feed port is located after the melting section of the twin-screw extruder, and the pre-drying conditions for the dual-modified SiO2 matting agent are drying at 100-120℃ for 2-4 hours.

8. The preparation method according to claim 4, characterized in that, The crystallization drying conditions described in step S3 are drying at 110-130℃ for 3-5 hours, and the moisture content of the masterbatch slices after drying is ≤50ppm.

9. The application of the masterbatch chips according to claim 1 in the preparation of matte polyester film, characterized in that, The masterbatch chips and glossy PET chips are mixed at a weight ratio of 10-20:80-90, and then melted, co-extruded in three layers, cast, biaxially stretched, and heat-set to obtain a matte polyester film.

10. The application as described in claim 9, characterized in that, The weight ratio of the masterbatch chips to the glossy PET chips is 15:85; three layers are co-extruded to form layers A, B, and C, wherein layers A and C are formed by a mixture of the masterbatch chips and glossy PET chips, and layer B is formed by pure PET. The thickness ratio of layers A, B, and C is 1:3:1; it is stretched longitudinally by 4.0 times at 85°C, stretched transversely by 4.0 times at 110°C, and heat-set at 230°C for 5 seconds; the thickness of the polyester matte film is 12-50μm, the gloss at 60° is ≤15GU, the haze is 40-70%, the tensile strength is ≥210MPa, and the elongation at break is ≥110%.

Citation Information

Patent Citations

  • Low-gloss matte polyester film and preparation method thereof

    CN112646323A

  • PET high-concentration matte master batch and preparation method thereof

    CN115073891A